Clinical relevance of performing endoscopic ultrasound‐guided fine‐needle biopsy for pancreatic neuroendocrine tumors less than 2 cm. Issue 7 (11th August 2020) - Heidsma, Charlotte M.; Tsilimigras, Diamantis I.; Rocha, Flavio; Abbott, Daniel E.; Fields, Ryan; Smith, Paula M.; Poultsides, George A.; Cho, Cliff; van Eijck, Casper; van Dijkum, Elisabeth Nieveen; Maithel, Shishir K.; Pawlik, Timothy M.; et al.
Abstract: Background: We sought to define the diagnostic yield and concordance rates between endoscopic ultrasound (EUS)‐fine‐needle aspiration (FNA) and surgical pathology specimen following resection of pancreatic neuroendocrine tumors (pNET) less than 2 cm. Methods: Patients with a pNET less than 2 cm who underwent EUS‐FNA were identified using a multi‐institutional international database. Tumor differentiation, and Ki‐67 index, as determined through EUS‐FNA were examined and concordance rates between EUS‐FNA and the surgical pathology were assessed. Results: Among 628 patients with a pNET less than 2 cm, 57.2% of patients had an EUS‐FNA performed. Patients who underwent EUS had slightly smaller size tumors (1.3 vs 1.4 cm), and the pNETs were less likely to be functional (15.3% vs 26.8%) or symptomatic (48.5% vs 56.5%) (both P  < .05). Among 314 patients with a pNET less than 2 cm who had an EUS‐FNA performed at the time of diagnosis, 243 (73.2%) had the diagnosis confirmed by preoperative EUS‐FNA. Tumor differentiation and Ki‐67 could be determined by EUS‐FNA in only 26.4% and 20.1% of patients, respectively. Concordance rate between EUS‐FNA and pathology was high relative to tumor differentiation (92.7%) and Ki‐67 (81.0%). Conclusion: Tumor differentiation and Ki‐67 index could be determined by EUS‐FNA in only 26.4% and 20.1% of cases, respectively. Further studies should focus on EUS techniques to optimize diagnostic yield and cell extraction in the preoperative setting.